The Impact of Mobile Technology on the learning of Management Science, and the Development of Problem-solving Skills. - Siow, Heng Loke; Cheng, Sheila (2015)
Learning is the construction of knowledge. E-learning is the application of information and communication technology (ICT) to make education accessible to learners who are physically not on-site. It is ubiquitous, enabling learners to study whenever they prefer and from wherever they are in the world. In the learning of problem solving skills through the subject of Management Science, the mobile technology plays an important role in enhancing students’ understanding and learning. This paper presents part of research findings of a sample of 15 students who are undergraduates and four facilitators in the class of Management Science. With the introduction of wireless and mobile technologies, the respondents have mixed opinion about the efficacy of mobile learning whether it could enhance or retard their learning of MS. The implications of the study are suggested.